The effect of higher estradiol levels during stimulation on pregnancy complications and placental histology. (August 2022) - Ganer Herman, Hadas; Volodarsky-Perel, Alexander; Ton Nu, Tuyet Nhung; Machado-Gedeon, Alexandre; Cui, Yiming; Shaul, Jonathan; Dahan, Michael H.
Abstract: Introduction: We aimed to assess obstetric outcomes and placental histology in stimulated in vitro fertilization (IVF) cycles with a high serum estradiol level. Methods: This was a historic cohort of live singleton deliveries after IVF, at a single university affiliated medical center between 2009 and 2017. Included were pregnancies following controlled ovarian stimulation with fresh embryo transfer. Excluded were IVF cycles with oocyte recipients and with a diagnosis of diminished ovarian reserve. High estradiol was defined as peak value above the upper quartile for the cohort, corresponding to 8700 pg/mL. Results: A total 147 deliveries in the higher estradiol group were compared to 427 deliveries in the control group. No differences were demonstrated in patient demographics and infertility workup, except for a significantly higher antral follicle count in the high estradiol group, 21.5 ± 13.1 vs. 17.3 ± 10.7 follicles, p < 0.001 and lower rate of single embryo transfer, 51.7% vs. 73.5%, p < 0.001. No differences were demonstrated between the groups in pregnancy and obstetric outcomes investigated, including gestational age, preterm delivery, preeclampsia, cesarean delivery, birthweight and low birth weight. Placental histological examination was notable for a higher rate of velamentous cord insertion in the higher estradiol group - 12.2% vs. 6.7%, p = 0.03, more so in a sub analysis of cases of very high estradiol - 15.7% vs. 7.3%, p = 0.02. Discussion: Placental histology following IVF with high estradiol level was notable for a higher rate of velamentous cord insertion. Highlights: Superovulation with resultant high estradiol may affect placentation. IVF with higher estradiol was not associated with adverse obstetric outcomes. A higher rate of velamentous cord insertion was noted with higher estradiol levels. Estradiol levels do not seem to alter placental pathology in other significant ways.